Perception of Direct and Indirect Compensations Fulfillment on Hazardous Work Environment - Chen, Chun-Hsi Vivian; Indartono, Setyabudi (Jurnal Ekonomi dan Pendidikan, 2012)
This paper investigates how ages, tenure, employee’s rank and work status related to perception of direct and indirect compensations fulfillment in a hazardous work environment. This study found that age, tenure, employee’s rank and work status are positively related to perception of direct and indirect compensations fulfillment. Implication for research and practice are discussed.